Comparison and Evaluation of Different Suture Materials used for the Post-Operative Closure Following Extraction of Third molars. - GOPALASAMY, KIRTANA; D, PRADEEP (The journal of contemporary issues in business and government, 2021)
Suture materials play a very important role in healing and enabling reconstruction and reassembly of tissue separated by the surgical procedure or trauma. Suture materials are used daily in oral surgery, and are considered to be substances most commonly implanted in the human body. Silk has been used as biomedical suture material for centuries and it provides important clinical repair options for many applications but the disadvantage is the biocompatibility problems .In the present day, Vicryl suture material is the most commonly used material in oral surgery, as it proves to be more biocompatible and plaque accumulation is reduced . Evaluation of 685 patients undergoing third molar extractions and evaluate the type of suture material given and compare between the different suture materials and their efficacy . Excel tabulation was done and SPSS results were derived .The study was able to evaluate and notice that Silk suture material was the most commonly given suture material and based it was also seen that the plaque accumulation was more in patients given silk sutures while Vicryl sutures was used the most post extraction of 18,28.From the present study we were able to conclude that Silk was the commonly used suture Material and the incidence of surgical site infection were greater in these patients . Of the 63 patients that were given Vicryl Sutures , there was no Surgical Site Infection (SSI) observed in any of the patients , this is attributed to the Antibacterial properties of Vicryl sutures that helps in avoiding surgical site infections ,